Post-Familial Families and the Domestic Division of Labor: A View From Australia - Hewitt, B; Western, M; Baxter, Janeen (My University, 2003)
This paper takes as its starting point recent claims by Beck-Gernsheim that we are living in an era of “post-familial families.” Beck-Gernsheim argues that our lives are no longer structured as they once were by tradition, class, religion and kin. Instead the family has become a transitional phase as individuals strive for fulfillment of personal goals and personal life projects. The demographic evidence to support these claims is clearly evident in relation to changing patterns of family formation and dissolution, as well as the movement of married women into paid employment. But what is less evident is a decline in traditional patterns of gender stratification within families. This paper uses recent national data from Australia to examine the relationship between post-familial status, as indicated by marital status and employment, and time spent on housework. The results show that gender is still a clear predictor of time spent on housework, but that within gender there is evidence that gender inequality may be declining in non-traditional households.
HILDA Survey Working Papers
Keywords: Families -- Work/family Balance; Families -- Composition; Activities; Activities -- Housework; Families; Families and relationships; Families and relationships